Iowa, spring 1997 documentations, June 11, 1997 - Iowa Ornithologists' Unionet al (1997)
A list of documented bird sightings organized by species, June 11, 1997. The list also contains the number of birds seen, date of sighting, location, and observer of each species. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed